Trusting children to enhance youth justice policy: The importance and value of children’s voices - Case, Stephen (2020)
Purpose: To explore the integration of children’s voices within youth justice policy and practice development. Design/methodology/approach: The authors theorise the efficacy of participatory practices in youth justice by presenting original empirical data drawn from innovative child friendly methodological approaches, including activity-oriented focus groups, questionnaires and in-depth interviews. Findings: Children’s voices have been noticeably absent from youth justice policy development in England. Children continue to be the recipients of adult-led, deficit-facing practices underpinned by a longstanding preoccupation with identifying and managing ‘risk’. These practices have undermined children’s knowledge and potential by distrusting their perspectives. In contrast, the internationally-relevant cogent arguments set out in this paper allude to the importance and benefits of engaging with children and listening to their voices in the planning and delivery of ‘Child First’ youth justice. Practical implications: It is recommended that youth justice professionals treat children in the Youth Justice System as children (not ‘offenders’), fostering non-hierarchical, empathic, trusting relationships with children, strengthen the child’s involvement in policy and practice processes and centralise their educative, health and wellbeing needs. Originality/value: The paper explores empirical examples from the emerging (but still limited) evidence-base of youth justice research studies that have placed the child’s voice at the centre of understanding their experiences at different stages of the Youth Justice System